Development and Evaluation of a Social Media Health Intervention to Improve Adolescents' Knowledge About and Vaccination Against the Human Papillomavirus - Rebecca R. Ortiz PhD; Autumn Shafer PhD; Joan Cates PhD; Tamera Coyne-Beasley MD (SAGE Publishing, 2018)
This study describes the formative research, execution, and evaluation of a social media health intervention to improve adolescents' knowledge about and vaccination against human papillomavirus (HPV). Based on the results from formative focus groups with adolescents (N = 38) to determine intervention feasibility, parameters, and message preferences, we developed and conducted a pretest/posttest evaluation of a 3-month social media health intervention for adolescents who had not completed the HPV vaccine series (N = 108). Results revealed that adolescents who fully engaged with the intervention improved in their knowledge compared with a control group, and many were also likely to have interpersonal discussions with others about what they learned. Adolescents are generally interested in receiving information about HPV and the vaccine, along with other relevant health information, through social media channels if messages are considered interesting, their privacy is protected, and the source is credible.